2019
DOI: 10.1111/cogs.12727
|View full text |Cite
|
Sign up to set email alerts
|

Is Emotional Magnitude Spatialized? A Further Investigation

Abstract: Accumulating evidence suggests that different magnitudes (e.g., number, size, and duration) are spatialized in the mind according to a common left–right metric, consistent with a generalized system for representing magnitude. A previous study conducted by two of us (Holmes & Lourenco, ) provided evidence that this metric extends to the processing of emotional magnitude, or the intensity of emotion expressed in faces. Recently, however, Pitt and Casasanto () showed that the earlier effects may have been driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In a typical SNARC effect, people respond faster to smaller numbers with the left hand and to larger numbers with the right, indexing a left-to-right mental number line. Beyond number, SNARC-like tasks have been used to test spatial mappings of many non-spatial domains, including size, brightness, auditory intensity, and even highly abstract domains like emotional intensity (Holmes, Alcat, & Lourenco, 2019;Macnamara, Keage, & Loetscher, 2018). These results have been widely interpreted as evidence of a "generalized magnitude system" (GMS; Walsh, 2003, p. 484).…”
mentioning
confidence: 99%
“…In a typical SNARC effect, people respond faster to smaller numbers with the left hand and to larger numbers with the right, indexing a left-to-right mental number line. Beyond number, SNARC-like tasks have been used to test spatial mappings of many non-spatial domains, including size, brightness, auditory intensity, and even highly abstract domains like emotional intensity (Holmes, Alcat, & Lourenco, 2019;Macnamara, Keage, & Loetscher, 2018). These results have been widely interpreted as evidence of a "generalized magnitude system" (GMS; Walsh, 2003, p. 484).…”
mentioning
confidence: 99%
“…However, the role of magnitude processing might become clearer in a parametric setting, using a range of pseudowords and shapes and thus sampling at multiple intervals along the rounded/pointed continuum (whilst accepting that the continuum might not be consistently mapped across individuals). Despite extensive overlap between brain regions involved in processing number-and sensory-based magnitude (Pinel et al, 2004), caution is indicated by recent challenges to the idea of a domain-general magnitude system (Anobile et al, 2018;Pitt and Casasanto, 2018; but see Holmes et al, 2019) which has been posited as an explanation for crossmodal correspondences (Lourenco and Longo, 2011;Spence, 2011;Sidhu and Pexman, 2018). Additionally, while we cannot rule out magnitude estimation as a possible explanation for the observed sound-symbolic incongruency effects, the regions of overlap between the magnitude estimation task and the incongruency effects are also implicated in multisensory attentional processes, which may ultimately turn out to be more important (see below).…”
Section: Magnitude Estimation Processesmentioning
confidence: 99%
“…While examples of symbolic non-numerical stimuli are relatively rare and can be found in music notation (Ariga & Saito, 2019;Fumarola et al, 2020;Prpic et al, 2016) and letters of the alphabet (Gevers et al, 2003), non-symbolic stimuli have been widely studied across different modalities. Most common examples are in the visual modality, with the size of pictorial figures Ren et al, 2011), luminance (Fumarola et al, 2014;Ren et al, 2011), angle magnitude (Fumarola et al, 2016) as well as emotional magnitude in facial displays (Holmes & Lourenco, 2011, Holmes et al, 2019; but see also Fantoni et al, 2019 andBaldassi et al, 2021). Numerous are also the examples in the auditory modality with pitch (Lega et al, 2020;Lidji et al, 2007;Pitteri et al, 2017;Prpic & Domijan, 2018;Rusconi et al, 2006), loudness (Bruzzi et al, 2017;Hartmann & Mast, 2017) and temporal aspects of the stimuli (Ishihara et al, 2008;De Tommaso & Prpic, 2020) being commonly investigated.…”
Section: Introductionmentioning
confidence: 99%